[LB.03.04] POPULATION-BASED REFERENCE VALUES FOR PULSATILE HEMODYNAMICS ACROSS THE ADULT LIFE SPAN. (September 2017) - Weber, T.; Wassertheurer, S.; Hametner, B.; Moebus, S.; Mahabadi, A.; Roggenbuck, U.; Lehmann, N.; Stang, A.; Joeckel, K.; Erbel, R.
Abstract : Objective: Pulsatile hemodynamics (central pressures, antegrade and backward waves, pulse wave velocity) are independent predictors of major cardiovascular events. Population-based reference values for wave separation analysis (WSA) based parameters (amplitude of forward wave–Pf and backward wave–Pb and their ratio reflection magnitude-RM) are currently missing. Design and method: In 2022 participants from the population-based Heinz Nixdorf Recall Study and the associated Multigeneration Study, untreated with antihypertensives, we performed high-fidelity radial tonometry, calibrated waveforms with brachial blood pressures and processed them with a validated transfer function. Pulse wave analysis (PWA; SphygmoCor system) yielded measures of incident pressure waves (P1) and wave reflections (Augmentation Index–AIx, Augmentation Pressure-AP). Using recently validated Windkessel-model based flow curves, WSA was performed, yielding Pf, Pb and RM (ARCSolver method). Aortic pulse wave velocity was estimated with a validated regression formula, including systolic blood pressure, age, and waveform characteristics. Results: 55.0% of participants were female, age range 19–88 years. A minority had diabetes (3.0%) or cardiovascular disease. Heart rate (mean values 67–72/min) was stable across all age groups. Brachial pressures were higher in men than in women (mean values 130/77 vs 120/72 mm Hg) up to 80 years of age, which was also true for central SBP. BPP increased only from 51 years upward, whereas cPP increased from youngest age groups across the entire adult life span. The difference was related to higher PP amplification in younger individuals. Central PP in women approached cPP in men in most age groups, due to lower PP amplification in women. Wave reflections increased across all age groups - Figure. The maximum increase was found in young and middle-aged individuals, when relative indices (AIx, RM) were considered. When absolute pressure increase was considered (Pb, AP), we observed a continuing increase. Gender differences (women having higher indices of wave reflection) were more profound with relative indices (AIx, RM) than with absolute measures (AP, Pb). PWV showed the most prominent increase with age in both sexes. Conclusions: We provide age- and gender specific reference values for central pulsatile hemodynamics in a general population cohort, untreated with antihypertensive drugs. Figure. No caption available.